Cost-effectiveness of gastric band surgery for overweight but not obese adults with type 2 diabetes in the U.S - Wentworth, John M (J Diabetes Complications, 2017)
AIM: To determine the cost-effectiveness of gastric band surgery in overweight but not obese people who receive standard diabetes care. METHOD: A microsimulation model (United Kingdom Prospective Diabetes Study outcomes model) was used to project diabetes outcomes and costs from a two-year Australian randomized trial of gastric band (GB) surgery in overweight but not obese people (BMI 25 to 30kg/m(2)) on to a comparable population of U.S. adults from the National Health and Nutrition Examination Survey (N=254). Estimates of cost-effectiveness were calculated based on the incremental cost-effectiveness ratios (ICERs) for different treatment scenarios. Costs were inflated to 2015 U.S. dollar values and an ICER of less than $50,000 per QALY gained was considered cost-effective. RESULTS: The incremental cost-effectiveness ratio for GB surgery at two years exceeded $90,000 per quality-adjusted life year gained but decreased to $52,000, $29,000 and $22,000 when the health benefits of surgery were assumed to endure for 5, 10 and 15 years respectively. The cost-effectiveness of GB surgery was sensitive to utility gained from weight loss and, to a lesser degree, the costs of GB surgery. However, the cost-effectiveness of GB surgery was affected minimally by improvements in HbA1c, systolic blood pressure and cholesterol. CONCLUSIONS: GB surgery for overweight but not obese people with T2D appears to be cost-effective in the U.S. setting if weight loss endures for more than five years. Health utility gained from weight loss is a critical input to cost-effectiveness estimates and therefore should be routinely measured in populations undergoing bariatric surgery.